Dynamic material flow analysis of silicon photovoltaic modules to support a circular economy transition. (28th March 2022) - Khalifa, Sherif A.; Mastrorocco, Benjamin V.; Au, Dylan D.; Ovaitt, Silvana; Barnes, Teresa M.; Carpenter, Alberta C.; Baxter, Jason B.
Abstract: Solar photovoltaics (PV) are the fastest growing renewable energy technologies for clean, cheap, and sustainable electricity generation. To prepare for rapid scale‐up, the PV industry needs to project material requirements to build out all aspects of the supply chain appropriately and plan to handle large volumes of module waste. Impacts of deploying different material circularity strategies to reduce waste and conserve primary resources need to be quantified to inform sustainable material management. Here, we introduce the photovoltaic dynamic material flow analysis (PV DMFA) model based on PV electricity generation. The model quantifies material flows and stocks in the cradle‐to‐cradle life cycles of utility‐scale c‐Si PV systems in the United States through 2100. We present case studies for solar flat glass and aluminum frame materials under various scenarios to project the impacts of PV performance, reliability, and processing parameters, material circularity strategies, and module design shifts. In the absence of circularity measures, 100 million MT of flat glass and 12 million MT of aluminum would be needed for PV installations by 2100 to meet projected growth in domestic utility PV demand to nearly 1000 TWh in 2100. With optimistic but feasible improvements in efficiency, reliability, and circularity, material intensity and waste could be reduced by nearly 50%. Efficient module collection, minimally intrusive recycling, and careful scrap handling and cleaning could improve material circularity in the PV value chain. This model serves as a sustainability data support tool that may aid in the circular economy transition for PV systems. Abstract : The open‐source photovoltaic dynamic material flow analysis (PV DMFA) model was developed to quantify stocks and flows of PV materials in their cradle‐to‐cradle life cycles based on U.S. utility‐scale PV electricity generation in the period 2000–2100. Case studies establish baselines and quantify impacts of PV parameters, potential circularity practices, and PV design shifts on flat glass and aluminum requirements and waste. Improving system reliability and scaling up robust recycling infrastructure is critical to promoting a circular economy for PV.